Migration and education: Child migrants in Bangladesh - Laura Giani (Sussex Migration Working Paper no. 33, 2006)
The paper examines the rural-urban migration patterns of children who move to Dhaka city, Bangladesh, either on their own or with their parents. It explores the consequences that the migration process driven by economic and social reasons has on children's education. The paper is based on a critical review of the available literature on child labour in Bangladesh and of academic studies on child labour migration. The findings of this work show that the inter-links between migration and education are more complex than the simple assumption that children's migration undermines their education and the literature suggests an ambivalent picture. However, poverty as well as the poor standards of education in the country, are strong arguments in explaining these linkages.